Properties and morphology of U-Polymer/PX-2000 polymer blends - Petrache, Christina A. (2007)
The thermal, mechanical properties and morphology of blends obtained by mixing U-Polymer and PX-2000 polymer were investigated by differential scanning calorimetry, dynamic mechanical analysis, mechanical tensile tests, Fourier Transform Infrared (FTIR) spectroscopy and scanning electron microscopy (SEM).U-Polymer and PX-200 polymer blends showed a single glass transition temperature and no melting temperature (Tm); the Tg-composition trend was interpreted by means of the Fox equation and Gordon-Taylor equation. The dynamic mechanical analysis of U-Polymer and PX-2000 polymer blend corroborated the results of the DSC of the blend having a single Tg and Tm suggesting that the blend in all the composition ranges investigated is homogeneous amorphous miscible blend. The tensile mechanical properties revealed that the presence of U-Polymer makes PX-2000 less brittle. Fractured surfaces were studied using a scanning electron microscopy. The SEM micrographs showed a homogeneous surface structure and no phase boundary between the U-Polymer and PX-2000 polymer, supporting the miscibility between these two polymers.